2004
DOI: 10.1590/s1519-38292004000100002
|View full text |Cite
|
Sign up to set email alerts
|

Fatores determinantes do crescimento infantil

Abstract: Esta revisão enfoca os fatores que interferem no crescimento de crianças nos primeiros anos de vida. Foram utilizadas informações de artigos publicados em revistas científicas, teses e publicações de organizações internacionais. O crescimento infantil se constitui em um dos melhores indicadores de saúde da criança e o retardo estatural representa atualmente, a característica antropométrica mais representativa do quadro epidemiológico da desnutrição no Brasil. Ressaltando a importância do fator genético no cres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
29

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 36 publications
(49 reference statements)
0
18
0
29
Order By: Relevance
“…Less than eight years of maternal study is considered as a risk factor for children's mortality together with the variables of prenatal care, and living in a risk area (2) . Level of education can have influence in determining growth because it is directly related with a better understanding of children care practices (13) . A study (14) found a strong association between maternal education and children's mortality, hospital admissions and anthropometric indicators (weight/age and height/age) of children up to 20 months old.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Less than eight years of maternal study is considered as a risk factor for children's mortality together with the variables of prenatal care, and living in a risk area (2) . Level of education can have influence in determining growth because it is directly related with a better understanding of children care practices (13) . A study (14) found a strong association between maternal education and children's mortality, hospital admissions and anthropometric indicators (weight/age and height/age) of children up to 20 months old.…”
Section: Discussionmentioning
confidence: 99%
“…As for the number of live births, it was equal to or higher than three, and stillborns were equal to or higher than one, this is considered one of the social risk factors for children mortality, together with the variables maternal age lower than 19, mothers with less than eight years of study, with no prenatal follow-up, or number of appointments lower than or equal to three, and delivery outside the hospital (2) . Family size and low income families with too many kids have been highlighted by international institutions such as the Food and Agriculture Organization of the United Nations, and the United Nations for Developing People, as conditions associated with nutritional risk, especially in developing countries (13) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Dentre os fatores extrínsecos, a situação socioeconômica, cultural, permeiam o crescimento infantil desde a fase pré-natal, podendo afetar o quadro nutricional da mãe durante a gravidez, e consequentemente retardo de crescimento intra-uterino e agravo interrelacionado com a prematuridade e com o baixo peso ao nascer e se constituem em importantes fatores intermediários do crescimento posterior da criança merecendo, portanto, destaque ao se avaliar o crescimento infantil. [1][2][3] A prematuridade, independentemente das características econômicas e sociais da família, implica em risco nutricional maior ao longo da infância, com todas as desvantagens que isso representa para o desenvolvimento do indivíduo. 1,4 Outro aspecto importante ligado ao crescimento físico e mudanças no estado nutricional de crianças refere-se ao aumento da prevalência de sobrepeso e obesidade na população infantil no Brasil 4,5 e no mundo.…”
Section: Introductionunclassified